2004
DOI: 10.1017/s0265051704005893
|View full text |Cite
|
Sign up to set email alerts
|

Music in a hospital setting: a multifaceted experience

Abstract: The article offers an explanation of the effects of music on children within a hospital setting and points up the multifaceted nature of this experience. The nature of the client group allows the musical experience to work on many different levels, such as modifying the child's perception of pain and reducing stress, whilst at the same time having an integral educational element that supports musical development. The evidence base is drawn from an extensive review of the music/medicine literature, interfaced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…Yet as they reflected more deeply on the work they were doing and as their confidence grew, they recognised the ways their informal music making linked to Key Competencies, and to music education objectives. Informal learning such as learning songs and developing rhythmic skills can occur without educational planning (Bunt, 1997;Preti & Welch, 2004) and the various elements involved in musical participation-the music, the setting, the participants-can all contribute to musical, social, inter or intrapersonal learning (Preti & Welch, 2004). Children respond enthusiastically to informal learning pedagogies that draw on their inherent learner agency (Power, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Yet as they reflected more deeply on the work they were doing and as their confidence grew, they recognised the ways their informal music making linked to Key Competencies, and to music education objectives. Informal learning such as learning songs and developing rhythmic skills can occur without educational planning (Bunt, 1997;Preti & Welch, 2004) and the various elements involved in musical participation-the music, the setting, the participants-can all contribute to musical, social, inter or intrapersonal learning (Preti & Welch, 2004). Children respond enthusiastically to informal learning pedagogies that draw on their inherent learner agency (Power, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the children's subjective experience of illness -rather than its severity -is one of the main factors influencing their psychological reaction to hospitalization (Ryan-Wenger, 1990;Cooper, Smaje & Arber, 1999;Kazak et al, 2006). These findings have implications for the analysis of the impact of musical interventions on the targeted population, as the effect of the music on the child cannot be isolated from the impact that the music has on the carers and, to some extent, on the hospital staff, because their interactions are mutually influenced by the presence of music (Preti & Welch, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in the field has shown that the genre and even composer and speed/ tempo of music are important factors in achieving intended outcomes of any music being played, and should thus be taken into account (Wakshlag, Reitz and Zillman 1982;Wolfe 1983;Mayfield and Moss 1989;Salamé and Baddeley 1989;Furnham and Allass 1999;Nittono, Tsuda and Nakajima 2000;Chebat, Chebat and Vaillant, 2001;Thompson, Schellenberg and Husain 2001;Husain, Thompson and Schellenberg 2002;Furnham and Strbac 2002;Cluphf and MacDonald 2003;Haynes 2003;Ivanov and Geake 2003;Preti and Welch 2004;Ziv & Goshen 2006).…”
Section: Introductionmentioning
confidence: 99%